Risks of Mycotoxins from Mycoinsecticides to Humans. (10th April 2016) - Hu, Qiongbo; Li, Fuxia; Zhang, Yuping
Abstract : There are more than thirty mycotoxins produced by fungal entomopathogens. Totally, they belong to two classes, NRP and PK mycotoxins. Most of mycotoxins have not been paid sufficient attention yet. Generally, mycotoxins do not exist in mycoinsecticide and might not be released to environments unless entomogenous fungus proliferates and produces mycotoxins in host insects or probably in plants. Some mycotoxins, destruxins as an example, are decomposed in host insects before they, with the insect's cadavers together, are released to environments. Many species of fungal entomopathogens have the endophytic characteristics. But we do not know if fungal entomopathogens produce mycotoxins in plants and release them to environments. On the contrary, the same mycotoxins produced by phytopathogens such as Fusarium spp. and Aspergillus spp. have been paid enough concerns. In conclusion, mycotoxins from mycoinsecticides have limited ways to enter environments. The risks of mycotoxins from mycoinsecticides contaminating foods are controllable.